Nacionalización y nacionalismo cotidiano: una panorámica - Claudio Hernández Burgos; Odilón Caldeira Neto (Historia Crítica)
Objective/context: Studies on nationalism have recently evolved toward a growing interest in nationalization. In particular, greater attention has been paid to the construction of national identities “from below” and to the multiple ways in which, in their daily lives, individuals reproduce, contest, or re-signify nationality. Starting from the theoretical framework of “everyday nationalism,” the main objective of this article is to offer a historiographical overview of the approaches to the study of nationalization and to gauge the usefulness of the theoretical contributions of everyday nationalism for different territories and chronological contexts. In particular, this paper highlights the relevance of directing attention to historical subjects’ individual agency and experiences of nationhood to understand key issues such as identity construction and the nationalization of society in their daily lives. Originality: This article evaluates the theoretical and methodological contributions of the so-called “everyday nationalism” as a way to connect the “micro” and “macro” levels and to capture, through subjectivities, the complexities inherent to the processes of construction of national identity and the multiple ways in which individuals received, answered, or re-signified the discourses and policies of nationalization promoted from power. Conclusions: This paper concludes by highlighting the potential of the “everyday nationalism” approach to gauge nationalization processes.